Alan Pastel Venture / Muhammad Aiman Jusoh - Jusoh, Muhammad Aiman (2020)
This case study will describe the entirely of the business in a several pages. Design to guide on the creation of the critical components of this document and provide examples of appropriate content for several section. I have picked one company in mind: Alan Pastel Venture.The company product-based oriented that are targeting ‘less budget but good material’ customer.The purpose of the case study is to identify the company with a capital starting of RM250,000 and below and yearly profit of RM120,000 and below (monthly of RM10,000 and below). The owner of the Alan Pastel Venture is an entrepreneur named Hafiz Safwan, an entrepreneur from Kelantan who pursue his dreams in big city, Selangor.